Hemobilia caused by a proper hepatic artery aneurysm opened into the choledochus. - Vergara, Mirtha; Schneeberger, Federico; Goller, Wolfgang (Cirugía del Uruguay, 1989)
Authors describe a case of hemobilia whose etiological diagnosis was made during an urgent laparotomy in the case of a proper hepatic artery aneurysm opened into the choledochus. They analyse etiology, clinical presentation, diagnostic methods, surgical procedures and prognosis of the afore mentioned aneurysms.